Chemical equilibria in a mixed solution of nickel and cobalt chloride - Lee, MS; Oh, YJ (JAPAN INST METALS & MATERIALS, 2005)
Ionic equilibria in the mixed solution of nickel and cobalt chloride were analyzed by considering the complex formation reactions, the mass and charge balance equations. The activity coefficients of solutes and water activity were calculated by using Bromley equation. Cobalt ion has a strong tendency to form various complexes with chloride ion, such as CoOCl3- and CoCl42, while NiCl+ was the only complex formed between nickel and chloride ion. Distribution of nickel and cobalt species with the compositions and pH values of the solution was obtained front the analysis of ionic equilibria in the mixed chloride solutions. The predicted pH values for NiCl2-CoCl-HCl-NaOH-H2O system agreed well with those measured at 298 K up to ionic strength of 9.53 mol/kg.
Keywords: MODIFIED BROMLEYS METHODOLOGY; THERMODYNAMIC PROPERTIES; SODIUM-SALTS; SEPARATION; D2EHPA